Microbiological Pollution Level and Seasonal Variations in Physicochemical Parameters of the River Buriganga, Dhaka - Karim, Md Abdul; Happy, Rehena Nasrin; Rasul, Md Saifur; Hoque, Sirajul (Bangladesh Journal of Microbiology, 2016)
The Buriganga is one of the highly polluted rivers in Bangladesh. Most of the industries and factories of Dhaka are situated on the banks of the river Buriganga or very close to the river system. Substantial part of urban sewage of the Dhaka city is also disposed in the river Buriganga. The study was conducted to determine the pollution level of water of river Buriganga. Field investigation was started from May 2010 and sample collection was conducted in different seasons up to June 2011. Various water quality parameters such as pH, DO, BOD, COD, TDS, Conductivity, Alkalinity, NO2 --N, NO3 --N, NH4+-N and PO4 -, were determined for water of each sampling points to monitor the level of these parameters where it exceeds or remain within the permissible limit. DO concentration of water of river Buriganga was very low ranging between 0.04 and 2.25 mg/l. The aerobic heterotrophic bacterial count ranged between 1.0 × 107 and 2.0 × 108 cfu/100 ml. The highest count of enteric bacteria was noticed during the autumn that was 2.0 × 105 cfu/100 ml. BOD and COD values along with the presence of different species of bacteria clearly indicated that the water of the river Buriganga is highly polluted with the organic, chemical and bacterial pollutants. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 11-15